Can Radiosensitivity Associated with Defects in DNA Repair be Overcome by Mitochondrial-Targeted Antioxidant Radioprotectors - Greenberger, Joel S.; Berhane, Hebist; Shinde, Ashwin; Rhieu, Byung H.; Bernard, Mark; Wipf, Peter; Skoda, Erin M.; Epperly, Michael W. (Frontiers in Oncology, 2014)
Radiation oncologists have observed variation in normal tissue responses between patients in many instances with no apparent explanation. The association of clinical tissue radiosensitivity with specific genetic repair defects (Wegner’s Syndrome, Ataxia Telangiectasia, Bloom’s Syndrome, and Fanconi Anemia) has been well established, but there are unexplained differences between patients in the general population with respect to the intensity and rapidity of appearance of normal tissue toxicity including radiation dermatitis, oral cavity mucositis, esophagitis, as well as differences in response of normal tissues to standard analgesic or other palliative measures. Strategies for the use of clinical radioprotectors have included modalities designed to either prevent and/or palliate the consequences of radiosensitivity. Most prominently, modification of total dose, fraction size, or total time of treatment delivery has been necessary in many patients, but such modifications may reduce the likelihood of local control and/or radiocurability. As a model system in which to study potential radioprotection by mitochondrial targeted antioxidant small molecules, we have studied cell lines and tissues from Fanconi Anemia (Fancd2-/-) mice of two background strains (C57BL/6NHsd, and FVB/N). Both were shown to be radiosensitive with respect to clonogenic survival curves of bone marrow stromal cells in culture and severity of oral cavity mucositis during single fraction or fractionated radiotherapy. Oral administration of the antioxidant GS-nitroxide, JP4-039, provided significant radioprotection, and also ameliorated distant bone marrow suppression (abscopal effect of irradiation) in Fancd2-/- mice. These data suggest that radiation protection by targeting the mitochondria may be of therapeutic benefit even in the setting of defects in the DNA repair process for irradiation-induced DNA double strand breaks.